Immunoblot analysis of immunoglobulin G response to the Lyme disease agent (Borrelia burgdorferi) in experimentally and naturally exposed dogs. - Greene, R T (1988)
Immunoblots were used to study the immunoglobulin G response to Borrelia burgdorferi in experimentally and naturally exposed dogs. Adsorption studies confirmed that the antibodies were specific for B. burgdorferi. Experimentally exposed dogs were asymptomatic. Naturally exposed dogs included both asymptomatic animals and animals showing signs compatible with Lyme disease. Naturally exposed dogs were from four geographic regions of the country. No differences were detected between immunoblot patterns of naturally exposed symptomatic or asymptomatic dogs from different areas of the country. The immunoblot patterns obtained with sera from experimentally exposed dogs were different from those obtained with sera from naturally exposed dogs and were characterized by reactivity to fewer and different protein bands. Immunoblot analysis using an OspA-protein-producing Escherichia coli recombinant showed that experimentally exposed dogs produced antibodies to OspA, whereas naturally exposed dogs did not. Modifications of the immune response over time, different routes of antigen presentation, and strain variation are factors postulated to account for the observed differences.